(untitled) (Journal of the College of Education for Women, 2019)
Labor movement is considered important in Britain because it is an international phenomenon of the feudal system and one of the flowerings of the era of the capitalist machine. At the beginning of the 18th century, the world witnessed a change and progress in many aspects of the industrial fields such as the different means of production .this era is called the industrial revolution which especially appeared in Britain and extended to other areas of the world .it leads to many changes in Europe and participated in different economic, political and cultural and social fields. and it has a very important role in progress and development but its disadvantage is that it is exploited by the capitalists to achieve their special rights .in other words ,it enables them to have power over the labors who have suffered poverty ,destitution and unemployment .as a result ,many thinkers ,intellectuals and labor leaders appear to form unions and associations that help to call for the labors right and deliver their voices to the highest levels under the name of " a trade union " .these unions ,associations and trade union are able to work as "a committee to represent workers " .it continues to do political work till it is able to reach the parliament and constitutes an independent party called "workers party " for the labor class in order to continue work for the sake of improving the conditions of the labors.